2006
DOI: 10.1007/s10038-006-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Longevity-associated NADH dehydrogenase subunit-2 237 Leu/Met polymorphism influences the effects of alcohol consumption on serum uric acid levels in nonobese Japanese men

Abstract: NADH dehydrogenase subunit-2 237 leucine/methionine (ND2-237 Leu/Met) polymorphism is reportedly associated with longevity in the Japanese population. The ND2-237Met genotype may confer resistance to cardiovascular and cerebrovascular atherogenic diseases. Hyperuricemia is one of the risk factors for cardiovascular disease. To investigate whether ND2-237 Leu/Met polymorphism is associated with serum uric acid (SUA) levels, we conducted a cross-sectional study in 321 healthy Japanese male subjects. In nonobese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Previous studies have found that both SBP and DBP were lower in non-drinkers with ND2-237Leu than in those with ND2-237Met (7), and that serum uric acid levels were lower in non-obese non-daily drinkers with ND2-237Leu than in those with ND2-237Met (11). Only among men with ND2-237Leu, habitual drinking was reportedly and positively associated with intraocular pressure (21).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have found that both SBP and DBP were lower in non-drinkers with ND2-237Leu than in those with ND2-237Met (7), and that serum uric acid levels were lower in non-obese non-daily drinkers with ND2-237Leu than in those with ND2-237Met (11). Only among men with ND2-237Leu, habitual drinking was reportedly and positively associated with intraocular pressure (21).…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of the ND2-237Met (Mt5178A) genotype is significantly higher in Japanese cen-tenarians than in the general population (3), and it is reported that Japanese individuals with ND2-237Met are more resistant to atherosclerotic diseases than those with ND2-237Leu (Mt5178C) (4)(5)(6). Moreover, ND2-237 Leu/Met polymorphism is associated with blood pressure (7), serum lipid levels (8,9), fasting plasma glucose levels (10) and serum uric acid levels (11), all of which are factors in atherosclerosis. In a study that excluded subjects taking antihypertensives, ND2-237 Leu/Met polymorphism was shown to modulate the effects of alcohol consumption on blood pressure (7).…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, the Mt5178 C/A polymorphism modulates the effects of alcohol consumption on blood pressure, 17 risk of hypertension, 10 serum triglyceride levels, 18 yearly changes in serum low-density lipoprotein (LDL) cholesterol levels 19 and serum uric acid levels. 20 Previous studies have also reported the combined effects of the Mt5178 C/A polymorphism and coffee consumption on the risk of hypertension 21 or abnormal glucose tolerance 22 in middle-aged Japanese men. For men with the Mt5178C genotype, X2 cups of coffee may reduce the risk of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the Mt5178A genotype, a genetic marker of mitochondrial haplogroup D, is significantly higher in Japanese centenarians than in the general population (Alexe et al 2007;Tanaka et al 1998) and it is reported that individuals with Mt5178A (mitochondrial haplogroup D) are less susceptible to lifestyle-related adult-onset diseases, for example hypertension (Kokaze et al 2007), diabetes (Wang et al 2001), metabolic syndrome ), myocardial infarction (Mukae et al 2003;Takagi et al 2004), and cerebrovascular diseases (Ohkubo et al 2002), than those with Mt5178C. Mt5178 C/A polymorphism is, moreover, also reported to be associated with blood pressure (Kokaze et al 2004a(Kokaze et al , 2007, serum lipid levels (Kokaze et al 2001(Kokaze et al , 2003a, fasting plasma glucose levels and glucose tolerance (Kokaze et al 2005a), serum uric acid levels (Kokaze et al 2006), intraocular pressure (Kokaze et al 2004b), hematological data (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2002(Kokaze et al , 2003b, and its interaction with smoking habits is associated with serum triglyceride levels (Kokaze et al 2003a), intraocular pressure (Kokaze et al 2004b), red blood cell counts (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2003b). As far as we are aware, however, no information is available about the relationship between Mt5178 C/A polymorphism and respiratory function or about its interaction with smoking habits in respiratory function.…”
Section: Introductionmentioning
confidence: 99%